Quantifying scientific jargon. (August 2020) - Willoughby, Shannon D.; Johnson, Keith; Sterman, Leila
When scientists disseminate their work to the general public, excessive use of jargon should be avoided because if too much technical language is used, the message is not effectively conveyed. However, determining which words are jargon and how much jargon is too much is a difficult task, partly because it can be challenging to know which terms the general public knows, and partly that it can be challenging to ensure scientific accuracy while avoiding esoteric terminology. To help address this issue, we have written an R script that an author can use to quantify the amount of scientific jargon in any written piece and make appropriate edits based on the target audience.